Remarks by World Bank Group President David Malpass to G20 Finance Ministers and Central Bank Governors at the 2022 Spring Meetings - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass to G20 Finance Ministers and Central Bank Governors at the 2022 Spring Meetings on April 20, 2022. He spoke about the following: (i) Global Economy and Risk; (ii) Global Health Issues; and (iii) International Financial Architecture.